2005
DOI: 10.1002/jbm.b.30417
|View full text |Cite
|
Sign up to set email alerts
|

Strontium‐containing hydroxyapatite (Sr‐HA) bioactive cement for primary hip replacement: An in vivo study

Abstract: The purpose of this study was to evaluate the strontium-containing hydroxyapatite (Sr-HA) cement in primary hip replacement, using a rabbit model, and to investigate the histological findings at the cement-implant and bone-cement interfaces under weight-bearing conditions. Unilateral hip replacement was performed with Sr-HA cement or polymethylmethacrylate (PMMA) cement in rabbits and observations were made after 6 months. Good fixation between the Sr-HA cement and implant was observed. Osseointegration of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
1
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 39 publications
(59 reference statements)
1
71
1
2
Order By: Relevance
“…Sr10-HAp has been widely studied in vitro and used in vivo, in particular as the main inorganic phase for the preparation of bone cement [32]. Pure, fully substituted SrHAp is also of special interest as the limiting case.…”
Section: Seeding Of Titrants In Sbfmentioning
confidence: 99%
“…Sr10-HAp has been widely studied in vitro and used in vivo, in particular as the main inorganic phase for the preparation of bone cement [32]. Pure, fully substituted SrHAp is also of special interest as the limiting case.…”
Section: Seeding Of Titrants In Sbfmentioning
confidence: 99%
“…Animals from each group were grafted subcutaneously with their respective materials (HA or ZnHA), and subdivided on groups of 5 individuals to be sacrificed at different experimental times (7,14,21,28 or 60 days after grafting). The rational for analysis of new biomaterials implies the cytotoxicity evaluations 14 , followed by the determination of subcutaneous response and intra-bony biocompatibility, as preconized by ISO 10993-5 and -6, former one applied in the present study.…”
Section: Experimental Groupsmentioning
confidence: 99%
“…Another important characteristic of HA is the possibility of incorporation of other components, such as metallic ions, on its structure [4][5][6] , thus promoting alterations on important physicochemical properties with impact on the biological response to this biomaterial. Also, this substitution may include bioactive elements or ions, which could also modulate important events related to bone regeneration, as they are released from HA onto biological media 7 . In this context, Zinc ions may represent strong candidates for incorporation on bioactive materials.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, for the cemented femoral component, there existed two interfaces, cement-prosthesis interface and bone-cement interface. Ni et al evaluated Sr-HA cement in primary hip replacement using a rabbit model for 6 months in which the histological findings at the cement-implant and bone-cement interfaces under weight-bearing conditions were investigated [20].…”
Section: In Vivo Evaluation For Primary Hip Replacementmentioning
confidence: 99%
“…Some studies indicated that strontium could be localized in calcified bone and it has been associated with improvement of osteoporosis [17][18][19]. Furthermore, this bioactive bone cement has shown improved contact with living bone when compared to commercial PMMA cement [20,21]. Sr-HA bioactive bone cement was designed to have desirable properties for use in treatment of spinal osteoporotic fractures by vertebroplasty [15,22].…”
Section: Introductionmentioning
confidence: 99%